History of intranasal splints. Issue 3 (30th January 2018) - Lau, J; Elhassan, H A; Singh, N
Abstract: Objective: Intranasal splints have long been utilised as a post-operative adjunct in septoplasty, intended to reduce the risk of adhesions and haematoma formation, and to maintain alignment during healing. Methods: A Medline literature review of the history and evolution of intranasal splint materials and designs was performed. Advantages and disadvantages of various splints are discussed. Results: Intranasal splints fashioned from X-ray film were first reported in 1955. Since then, a variety of materials have been utilised, including polyethylene coffee cup lids, samarium cobalt magnets and dental utility wax. Most contemporary splints are produced from silicon rubber or polytetrafluoroethylene (Teflon). Designs have varied in thickness, flexibility, shape, absorption and the inclusion of built-in airway tubes. Future directions in splint materials and designs are discussed. Conclusion: Intranasal splints have steadily evolved since 1955, with numerous novel innovations. Despite their simplicity, they play an important role in nasal surgery and will continue to evolve over time.